Reducing credit constraints to post-secondary technical education in developing countries : Evidence from Colombia - Gamboa, Luis Fernando (2018)
We assess the importance of credit constraints for post-secondary education using different discontinuities that affect enrollment in free-technical education and eligibility for educational grants in Colombia. Our strategy makes use of multiple RD estimators in order to identify the importance of covering the opportunity cost on enrollment, completion and access to formal labor market for poor young individuals who want to enter tertiary education. We find evidence of large increases in enrollment and graduation rates. Particularly, the probability of obtaining a certification in technical studies rises from 3% to 14%. We also find an important increase in formal labor market participation in the medium term, individuals who received monetary aid to enroll and finish technical education from 2014 to 2016 are 50% more likely to have a formal job in 2017. We find that reducing credit constraints has no differential effects with respect to educational variables but only affects the labor market of men.